Rancang Bangun Sistem Peringatan Pendeteksi Halangan Gerak Swing Pada Swing Area Berbasis Arduino Uno dengan Sensor Ultrasonik Untuk Excavator - Anyuca, Herbudi Bagas; Ismail , Andhi Akhmad (Department of Mechanical Engineering, Vocational College, Gadjah Mada University., 2024)
Occupational health and safety, especially in heavy equipment projects, is very important to avoid work accidents. In the field of construction and mining, work accidents that are often experienced are usually run over, and hit. Most of these accidents are caused by operator or human negligence factors, as well as factors from machines or tools. On the hydraulic excavator there is a swing movement, this movement has the potential to cause work accidents such as hitting an object in the swing area because the object is in blind spots that cannot be measured and seen by the operator. In this study, the authors designed a tool that functions as a warning system and monitoring for detecting swing motion obstacles in the swing area to avoid the accident, while testing the performance of the system that has been created. The design of this tool uses an ultrasonic sensor HC SR-04 which is able to detect an object with ultrasonic waves, LCD 1602 as a monitoring tool for the distance between the sensor and the object that blocks the swing motion, and with the addition of a buzzer as a warning system that will sound at a certain distance. Thus the operator can anticipate if there are objects that block the swing motion. The overall test results of the system that has been created show that the front section obtained a test success rate of 84% with a standard deviation of 0.3116, and the back section obtained a test success rate of 86% with a standard deviation of 0.2916.